2015
DOI: 10.5433/1679-0359.2015v36n2p943
|View full text |Cite
|
Sign up to set email alerts
|

Características de carcaça e carne de novilhos de diferentes predominâncias genéticas alimentados com dietas contendo níveis de substituição do grão de milho pelo grão de milheto

Abstract: ResumoObjetivou-se avaliar as características de carcaça de tourinhos mestiços europeus ou zebuínos, alimentados em confinamento com rações com elevada proporção de concentrado (80%) contendo diferentes teores de grão de milheto moído em substituição ao grão de milho moído (0, 33, 66 e 100%). Foram confinados, em 16 baias coletivas, 45 tourinhos com predominância genética Aberdeen Angus e 44 tourinhos com predominância genética Nelore, com peso médio inicial de 317,8 e 320,7 kg, respectivamente, e 21 meses de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
5
6
0
2
Order By: Relevance
“…The lack of variation for average daily gain, final body weight, and hot carcass weight between steers fed pearl millet-and corn-based diets (Table 7) was consistent with those observed in other studies (Gonçalves et al, 2010;Silva et al, 2014;Silva et al, 2015); in fact, most studies have demonstrated similar productive performance of animals fed diets containing corn grain and diets containing pearl millet grain. Moreover, the variation in feed conversion reflects the variation in the DM intake with increasing concentration of dietary BMB, which was also reported by Miotto et al (2013).…”
Section: Discussionsupporting
confidence: 79%
“…The lack of variation for average daily gain, final body weight, and hot carcass weight between steers fed pearl millet-and corn-based diets (Table 7) was consistent with those observed in other studies (Gonçalves et al, 2010;Silva et al, 2014;Silva et al, 2015); in fact, most studies have demonstrated similar productive performance of animals fed diets containing corn grain and diets containing pearl millet grain. Moreover, the variation in feed conversion reflects the variation in the DM intake with increasing concentration of dietary BMB, which was also reported by Miotto et al (2013).…”
Section: Discussionsupporting
confidence: 79%
“…The results of this study were similar to those obtained by Miotto et al (2012a), who found a carcass muscular reduction from the reduction of cushion thickness to the increment of BMB level in the diet, but found no differences in longissimus dorsi area and carcass conformation. The results were also consistent with those obtained by Silva et al (2015), who found no change in conformation, longissimus dorsi area and thickness of bovine carcass fed with diets containing corn replacement levels for millet.…”
Section: Resultssupporting
confidence: 91%
“…From the results obtained and presented in the literature (MIOTTO et al, 2012a;CRUZ et al, 2015a), it is assumed that in addition to the BMB level in the diet, food nutritional characteristics (notably the energy content) replaced by BMB in the diet are keys factors affecting body development and consequently carcass weight of feedlot cattle. Further, the results obtained between corn-or millet-based diets for the cold carcass weight are consistent with those obtained by Silva et al (2015), who found no change in cattle carcass weight fed with varying millet levels (0, 33, 66, and 100%) replacing corn. Carcass yield was unchanged (P > 0.05) with increasing levels of BMB in the diet.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations